Understand role of COVID‐19 in contractual obligations - O'Brien, Timothy (College Athletics and the Law, 2020)
It's common knowledge: COVID‐19’s impact on student‐athletes, coaches, and staff members of every athletics department has been substantial. At the same time, however, the legal and business sides of an athletics department's operations are truly at the epicenter of much of the required activity. Indeed, in regard to other campus departments, only a few have as many daily, weekly, and ongoing contractual obligations with outside entities as athletics. The true magnitude of the business side of athletics became quickly apparent when existing arrangements for trips, hotels, buses, planes, equipment, supplies, food, services, and support personnel for numerous teams had to be canceled within a short period of time. Although cancellations took care of the short‐term commitments, athletics departments still need to address many broader and potentially more impactful contractual obligations.